Synthesis Of Gallium Nitride (GaN) Nanostructures By Electrochemical Techniques For Sensing Applications - Al-Heuseen, Khalled Mhammad Kallef (2011)
The main goal of this work presented in this thesis was to fabricate nanostructures of GaN using two low-cost electrochemical techniques namely photoelectrochemical etching (PECE) and electrochemical deposition (ECD). In the first category of this work, the porous GaN was generated using photoelectrochemical etching techniques under different conditions, i.e. current density, different duration of etching and different electrolytes. The results showed that the average pore size was sensitive to the current density, and different electrolytes generated different morphology.